The National Democratic Government and tourism development in Ghana: A retrospection - Yobo Opare-Addo (Bahasa Indonesia, 2023)
Ghana came under democratic rule from 1993-2000 after the National Democratic Congress (NDC) had won the general election conducted in December 1992. Flt. Lt. J.J. Rawlings, the Party’s leader became the President of the Fourth Republic. It was refreshing to see Ghanaians embrace democracy with renewed energy, zeal and enthusiasm. Meanwhile the tourism industry was perceived to grow at a rate of between 12% and 16% and a less costly export item. The new government undertook measures and policies to improve the tourism industry and at the same time embarked on export diversification to reap the foreign exchange that the industry could generate. The objective of this paper is to examine the measures and policies of the NDC to improve the tourism industry in order to reap the foreign exchange focusing on the role of the government as an agent of tourism development, creation of conducive environment for tourism to flourish, the provision of tourism facilities and political stability and how these factors impacted on the tourism industry in Ghana. In the final analysis an assessment is made on the NDC Government’s contribution towards tourism development.